Strategies for improving patient outcome in patients with familial adenomatous polyposis. (February 2014) - Latchford, Andrew; Phillips, Robin
<x xml:space="preserve">Abstract</x> Introduction: Familial adenomatous polyposis (FAP) is a rare condition, characterised by the development of multiple adenomatous polyps in the colon and rectum but which also displays a number of extra-colonic manifestations. Undoubtedly, there have been major advances in our understanding and management of FAP. However, despite these advances patients with FAP have a fourfold mortality rate when compared with the general population. Areas covered: The published literature has been critically appraised, focusing on four main areas: genetic aspects of FAP, management of the colorectum, understanding and management of desmoids tumours and the management of duodenal disease in FAP. The progress in these areas that has been made over recent years has then been described, with regard to our scientific understanding as well as clinical management of the condition. Expert opinion: Expert opinion is provided regarding on-going clinical dilemmas. In particular, the expert opinion focuses on clinical management and areas of research that are required, which may directly influence clinical management of this condition, thereby improving the outcome of patients with FAP.